Good Clean Living: Calgary Modern 1947–1967 - Ball, Norman R. (Archivaria, 2000)
This article reviews the exhibition Calgary Modern 1947–1967 at the Nickle Arts Museum, University of Calgary. The exhibition examines modern architecture during a critical period of growth in a city whose history is largely defined by progressive, optimistic modernism. The exhibition is organized around eight related areas: introduction, office, housing, house, worship, education, leisure, and infrastructure. The article contends that Calgary Modern 1947–1967 was imaginatively and cleanly designed. The exhibition is complemented by a publication of the same name. RÉSUMÉ L’exposition Calgary Modern 1947-1967, tenue au Nickel Arts Museum del’université de Calgary, porte sur l’architecture moderne au cours d’une période critique de croissance d’une cité dont l’histoire est largement définie par un modernisme progressiste et optimiste. L’exposition est bâtie autour de huit thèmes interreliés: une introduction, le bureau, le logement, la maison, la religion, l’éducation, le loisir et les infrastructures urbaines. L’exposition a été montée de façon intelligente et sobre; elle est soutenue par une publication qui porte le même titre.